Prevalence of recurrent aphthous stomatitis in western population of Maharashtra, India - Yojari R Rajmane; S R Ashwinirani; Girish Suragimath; Ajay Nayak; Vijaya S Rajmane; Mohini Lohana (Wolters Kluwer Medknow Publications, 2017)
Aim: Recurrent aphthous stomatitis (RAS) is characterized by recurrent painful, single, multiple ulcers appearing in oral mucosa. Various studies have been conducted to find the prevalence of RAS worldwide. Till now, no studies have been conducted to report the prevalence of RAS in Maharashtra. The aim of the present study was to evaluate the prevalence of RAS in western population of Maharashtra. Materials and Methods: A total of 71,851 patients within the age group between 10 and 70 years were screened for a period of 5 years from March 2011 to March 2016 in western population of Maharashtra. Collected data were recorded and entered, verified, processed, and analyzed using software package SPSS program version 19. The frequency and distribution of RAS in gender, age, and site were calculated. Results: Out of 71,851 patients, only 72 patients were clinically diagnosed to be suffering from RAS. The prevalence of RAS was 0.1%. There was a higher prevalence in females as compared to males and it was most common in the second and third decades of life, with buccal mucosa as the predominant site followed by labial mucosa and tongue. Conclusion: Based on the results of our study, the prevalence of RAS in western population of Maharashtra was 0.1%, which was very low as compared to other Indian population. Females were more commonly affected. The most common age affected in our study group was second and third decades. The most common site was buccal mucosa followed by labial mucosa and tongue.